Pengaruh Struktur kepemilikan terhadap Sustainability Reporting dengan Usia Perusahaan sebagai Moderasi - Mayang Apriliani; Maylia Pramono Sari (Politeknik Ganesha Medan, 2026)
Sustainability reporting in accordance with the Global Reporting Initiative (GRI) standards has been widely recognized as a common framework for transparently communicating corporate economic, environmental, and social performance. However, concerns remain that such reporting may focus more on disclosure than on the actual implementation of sustainability practices. This study aims to investigate the association between ownership structure, managerial, institutional, and foreign ownership, and the extent of sustainability reporting, with firm age serving as a moderating variable. The scope of this paper is limited to data collected from manufacturing entities registered on the Indonesia Stock Exchange (IDX) over the period of 2022–2024. Employing purposive sampling, 53 firms were selected, resulting in 152 observations. The data were analyzed using moderated regression analysis (MRA) with the assistance of EViews 12 software. The findings reveal that managerial, institutional, and foreign ownership have a statistically significant negative effect on sustainability reporting. While firm age significantly weakens the association between managerial ownership and sustainability reporting, it does not moderate the effects of institutional or foreign ownership. Legitimacy theory helps this study explain sustainability reporting. It shows how ownership structure affects direct and moderating relationships. Theoretically, this research contributes to the existing literature by using Legitimacy Theory to explain the direct and moderating effects on sustainability reporting. In this regard, symbolic legitimacy theory and substantive legitimacy theory explain the factors influencing sustainability reporting. Practically, this research delivers practical implications for corporate managers, investors, and regulators by emphasizing the role of aligning ownership structures and considering firm characteristics, particularly firm age.